2020
DOI: 10.3892/or.2020.7826
|View full text |Cite
|
Sign up to set email alerts
|

Beige adipocytes contribute to breast cancer progression

Abstract: Adipocytes are the main stromal cells in the mammary microenvironment, and crosstalk between adipocytes and breast cancer cells may play a critical and important role in cancer maintenance and progression. Tumor-induced differentiation to beige/brown adipose tissue is an important contribution to the hypermetabolic state of breast cancer. However, the effect of epithelial cell-beige adipocyte communication on tumor progression remains unclear. To contribute to the understanding of this phenomenon, we character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Adipocytes are the main stromal cells in the mammary microenvironment, and crosstalk between adipocytes and cancer cells may play a critical and important role in cancer maintenance and progression. Tumor induced differentiation to beige/brown adipose tissue is an important contribution to the hypermetabolic state of breast [20] and prostate [7] cancer, but still the bibliography says nothing about browning and kidney cancer. And, the effect of epithelial cell-beige adipocyte communication on tumor progression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adipocytes are the main stromal cells in the mammary microenvironment, and crosstalk between adipocytes and cancer cells may play a critical and important role in cancer maintenance and progression. Tumor induced differentiation to beige/brown adipose tissue is an important contribution to the hypermetabolic state of breast [20] and prostate [7] cancer, but still the bibliography says nothing about browning and kidney cancer. And, the effect of epithelial cell-beige adipocyte communication on tumor progression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Both due to phenotypic modi cations of the peritumoral adipose tissue, and due to changes in the expression of genes involved in the browning process [17-19;7;20]. Gantov et al recently demonstrated that beige adipocytes favor tumor progression of mouse mammary epithelial cell lines, both tumor and non-tumor [20]. Our group recently demonstrated that renal peritumoral AT (hRAT) favors tumor progression through soluble factors that it secretes into the microenvironment, unlike normal renal adipose tissue (hRAN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reciprocal interaction of the adipose microenvironment and breast cancer tissue is a critical factor in promoting cancer cell migration [ 50 ]. Experimental results showed that adipose cells led to a decrease in the viability of myoepithelial cells (MECs), which are known as tumor suppressor cells that block the transition from ductal carcinoma in situ to invasive carcinoma.…”
Section: Lep Somatic Mutations and Cancermentioning
confidence: 99%
“…CIDEA and ADIPOQ are highly expressed in breast tissue and adipose tissue, and both of them could promote apoptosis of tumour cell lines and might inhibit tumour growth [26]. However, research supports that CIDEA participates in the interaction of tumour and nontumour mouse mammary epithelial cells, ultimately accelerating tumour progression [27]. In addition, a relevant point worth mentioning is that the adiponectin-AdipoR1 axis was defined as a predictor of tyrosine kinase inhibitor resistance in metastatic renal cell carcinoma [28]…”
Section: Some Drug Resistance Research Associated With Cancer Indicated That the Gene Fusion Of Esr1-akap12 Induces Osimertinib (A Kind Omentioning
confidence: 99%